2018
DOI: 10.13045/jar.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Conventional and Korean Medicine for Multiple Vertebral Compression Fractures Associated with Postpartum Osteoporosis: A Case Report

Abstract: Multiple vertebral compression fractures are a rare condition and are a serious consequence of postpartum osteoporosis. This report describes the case of a 35-year-old woman who had given birth to her first child 2 months before the onset of pain. Magnetic resonance imaging showed compression fractures of 7 vertebrae. The patient was treated with both conventional, and Korean medicine methods including acupuncture and herbal prescriptions. The patient's progress was assessed using self-reported symptoms, scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Thus, studies involving long-term follow-up based on imaging tests for compression rate, kyphotic angle, and pain intensity are recommended. The study by Lee et al [22] is noteworthy because although improvements in cold sensation were observed, according to the EQ-5D assessment, the quality of life obviously deteriorated. Compression fractures can have a psychological impact; therefore, future research should address the improvement in physical issues and the long-term quality of life through traditional Korean medicine treatments.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, studies involving long-term follow-up based on imaging tests for compression rate, kyphotic angle, and pain intensity are recommended. The study by Lee et al [22] is noteworthy because although improvements in cold sensation were observed, according to the EQ-5D assessment, the quality of life obviously deteriorated. Compression fractures can have a psychological impact; therefore, future research should address the improvement in physical issues and the long-term quality of life through traditional Korean medicine treatments.…”
Section: Discussionmentioning
confidence: 92%
“…The 16 included studies (Tables 1, 2) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were classified according to the journal and year of publication, patient information, intervention, evaluation methods, and treatment results.…”
Section: Discussionmentioning
confidence: 99%